Implementasi Kebijakan Pengembangan Transportasi Publik Melalui Program Wira Wiri Kota Surabaya - Nabila Aulia Ayu Rahmatika; Rudy Handoko; Muhammad Roisul Basyar (Lembaga Pengembangan Kinerja Dosen, 2024)
Public transportation is one of the needs that must be met for every human being who carries out daily activities, so the government needs to pay attention to its development. The city of Surabaya is one of the cities with high traffic jams, which is one of the reasons for developing public transportation. Wira Wiri Suroboyo, which was inaugurated last year, brought enthusiasm from the public but also experienced a decline in passengers in the second month of its launch. The explanation explained by the Transportation Service regarding the decrease in the number of passengers is that it coincides with the fasting month which means not many people travel. However, if compared with the number of people in Surabaya City, the use of Wira Wiri Suroboyo transportation is still not fulfilled. Public interest in using public transportation is considered lacking. This research was conducted to determine the success of implementing public transportation development policies through the Wira Wiri Suroboyo program. This research uses qualitative methods with observations at the Transportation Service through interviews and taking documentation. The results of this research are that the implementation of public transportation development through Wira Wiri Suroboyo can be said to be successful, seen from the increase in the number of passengers.